A Graphic Method for Computing Multi-Atomic Resonant Photoemission Cross Section (Journal of Atomic and Molecular Sciences, 2015)
A graphic method for studying multi-atom resonant photoemission processin molecules and solids is presented in this work. The Feynman diagrams have beenapplied to describe the interactions between atoms in MnO molecules. The theoreticalresults show that the resonant contribution exhibits a strong distance-independent andelement specific effects for the neighboring atoms. Two mechanisms, the interactionsbetween the atoms and the reabsorption process have been supposed in the presentwork to explain the multi-atomic resonant photoemission for the first time.